Ekspresi Cyclooxygenase-2 pada Adenokarsinoma Asinar Prostat, High-Grade Prostatic Intraepithelial Neoplasia dan Benign Prostatic Hyperplasia - Meiske Margaretha; I Gusti Alit Artha; Herman Saputra (Majalah Patologi Indonesia, 2018)
ABSTRAK Latar belakang Cyclooxygenase-2 (COX-2) adalah isoenzim yang mengkatalitis perubahan asam arakidonat menjadi prostaglandin yang merupakan mediator proses inflamasi. Enzim ini memiliki peranan dalam patogenesis dan karsinogenesis pada beberapa organ di antaranya prostat. Peningkatan ekspresi COX-2 dikaitkan dengan prognosis yang buruk pada keganasan prostat. Penelitian ini dilakukan untuk menganalisis ekspresi COX-2 pada benign prostatic hyperplasia (BPH), high-grade prostatic intraepithelial neoplasia (HGPIN) dan adenokarsinoma asinar prostat (AAP). Metode Penelitian ini dilakukan di Bagian/SMF Patologi Anatomik Fakultas Kedokteran Universitas Udayana/RSUP Sanglah Denpasar dan Bagian/SMF Patologi Anatomik Fakultas Kedokteran Universitas Gadjah Mada/RS Dr. Sardjito Yogyakarta sejak tanggal 1 Januari 2012 sampai dengan 31 Januari 2014 menggunakan metode observasional analitik potong lintang dengan total sampel sebanyak 48 yang terdiri dari 16 sampel kelompok BPH, 16 sampel kelompok HGPIN dan 16 sampel kelompok adenokarsinoma asinar prostat. Perbedaan ekspresi COX-2 pada masing-masing kelompok dianalisis dengan uji Kruskal-Wallis dan chi-square. Hasil Ekspresi COX-2 pada adenokarsinoma asinar prostat lebih tinggi dibandingkan pada BPH (p=0,000). Ekspresi COX-2 pada adenokarsinoma asinar prostat lebih tinggi dibandingkan pada HGPIN (p=0,000). Kesimpulan Ekspresi COX-2 berperan dalam patogenesis adenokarsinoma asinar prostat, HGPIN dan BPH. Kata kunci: adenokarsinoma asinar prostat, BPH, COX-2, HGPIN. ABSTRACT Background Cyclooxygenase-2 (COX-2) is an isoenzyme which catalyzes the tranformation of arachidonic acid to prostaglandin which is mediator of inflammation process. This enzyme plays a role in pathogenesis and carcinogenesis in some organs including prostate. Increased expression of COX-2 is associated with poor prognosis in prostate malignancy. This study was to analyzed COX-2 expression in benign prostatic hyperplasia (BPH), high-grade prostatic intraepithelial neoplasia (HGPIN) and prostatic acinar adeno-carcinoma. Methods This study was performed in Department of Anatomical Pathology Faculty of Medicine University of Udayana/Sanglah General Hospital Denpasar and Department of Anatomical Pathology Faculty of Medicine University of Gadjah Mada/Dr. Sardjito General Hospital Yogyakarta from January 1st 2012, untill January 31, 2014. This study was an observational analytic cross-sectional study with a total samples of 48 total which comprised of 16 samples of BPH, 16 samples of HGPIN and 16 samples of prostatic acinar adenocarcinoma. Differentiation of COX-2 expression in each group, were analyzed by Kruskal-Wallis test and chi-square test. Results The results of this study showed that COX-2 expression was higher in acinar adenocarcinoma of the prostate compared with BPH (p=0.000) and COX-2 expression was higher in acinar adenocarcinoma of the prostate compared with HGPIN (p=0.000). Conclusion COX-2 expression plays a role in the pathogenesis of acinar adenocarcinoma of the prostate, HGPIN and BPH. Key words: acinar adenocarcinoma of prostate, BPH, COX-2, HGPIN.